A two-component regulatory system playing a critical role in plant pathogens and endosymbionts is present in Brucella abortus and controls cell invasion and virulence - Sola-Landa, Alberto (1998)
Two mutants showing increased sensitivity to polycations and surfactants were obtained by transposon mutagenesis of virulent Brucella abortus 2308 Nal(r). These mutants showed no obvious in vitro growth defects and produced smooth-type lipopolysaccharides. However, they hardly multiplied or persisted in mouse spleens, displayed reduced invasiveness in macrophages and HeLa cells, lost the ability to inhibit lysosome fusion and were unable to replicate intracellularly. Subsequent DNA analyses identified a two-component regulatory system [Brucella virulence related (Bvr)] with a regulatory (BvrR) and sensory (BvrS) protein. Cloning on bvrR in the BvrR-deficient mutant restored the resistance to polycations and, in part, the invasiveness to polycations and, in part, the invasiveness and the ability to multiply intracellularly. BvrR and BvrS were highly similar (87-89% and 70-80% respectively) to the regulatory and sensory proteins of the chromosomally encoded Rhizobium meliloti Chvl-ExoS and Agrobacterium tumefaciens Chvl-ChvG systems previously shown to be critical for endosymbiosis and pathogenicity in plants. Divergence among the three sensory proteins was located mostly within a periplasmic domain probably involved in stimulus sensing. As B. abortus, R. meliloti and A. tumefaciens are phylogenetically related, these observations suggest that these systems have a common ancestor that has evolved to sense stimuli in plant and animal microbial environments.